Efficiency of a 3-week multicomponent rehabilitation on improving the function in a patient with Friedreich’s ataxia – a case report - Samardžić, Vesna (Vojnosanitetski pregled, 2023)
Introduction. Friedreich’s ataxia (FA) is an autosomal re-cessive neurodegenerative disease. Ataxia, as the cardinal symptom, affects the trunk, with swaying, imbalance, and falls, as well as the limbs, with increasing difficulty in ac-tivities of daily living. Physical therapy has been recog-nized as a means of managing physical symptoms and maximizing function in affected persons. To our knowledge, there are no studies that have evaluated the ef-fectiveness of proprioceptive neuromuscular facilitation (PNF) stabilization techniques in the rehabilitation of pa-tients with such a diagnosis. Case report. We present a 26-year-old female with FA who had severe truncal and limb ataxia, speech difficulty, and poor walking ability. During the three-week rehabilitation, an individually tai-lored physical therapy program based on PNF stabilization techniques was applied. The implemented rehabilitation program resulted in an overall functional improvement. The reduction in ataxia was registered according to the Scale for the Assessment and Rating of Ataxia (SARA). The Functional Independence Measure (FIM) instrument – a component of locomotion, revealed greater independ-ence in walking. Conclusion. A rehabilitation program based on PNF stabilization techniques may reduce ataxia and improve walking ability in patients with FA.